A new annotation system based on a semantic analysis of a learner's annotative activity to invoke web services. (27th October 2014) - Kalboussi, Anis; Mazhoud, Omar; Omheni, Nizar; Kacem, Ahmed Hadj
Many annotation systems proposed in the literature suffer from an under–exploitation of the annotation's semantic at the level of the assistance presented to the learner during annotative activity. Thus, these tools offer the same classic features to its users, such as management, search, sharing and storage of annotations. In this paper, we propose a new annotation system which differs in its novel features. The system tries to assist the learner via web services during learning activities. Therefore, from a user's annotation, our system is able to interpret a goal implicitly expressed and tries to discover and invoke a web service that can meet this annotation's objective. This system is based on an annotation model composed of an ontology and pattern annotation. This enrichment will provide advantages for both the provider, who will find his service within the consumer's reach, and the learner, who will have at his disposal an intelligent annotation tool.